Characterisation of the haemodynamic effects of cannabidiol in humans using duplex ultrasound and other techniques - Sultan, Salahaden (2020)
The two main phytocannabinoids, ∆9-Tetrahydrocannabinol (THC) and Cannabidiol (CBD) are agents already licensed for clinical use (i.e. Sativex®and Epidiolex®). THC and CBD have numerous cardiovascular effects in vitro; however, their effects on haemodynamics in vivoin humans remain unclear.